2010
DOI: 10.1585/pfr.5.040
|View full text |Cite
|
Sign up to set email alerts
|

Forced Magnetic Reconnection in Helical Plasmas

Abstract: Magnetic islands excited by resonant magnetic perturbations (RMPs) in helical plasmas are investigated. A Rutherford-type equation is coupled with the time evolution equation of the radial electric field associated with the neoclassical particle diffusion due to helically rippled magnetic fields. Using the model, bifurcation between the excitation and the annihilation of non-rotating magnetic islands are newly observed, depending on the magnitude of RMPs and the anomalous plasma viscosity. It is found that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…However, influence of neoclassical transport has not been discussed so far. In our previous study, using a theoretical model, it is shown that the self-healing of islands is clearly reproduced, when the neoclassical transport-driven poloidal flows is taken into account [5]. In this paper, we report that such mechanism is actually observed in reduced fluid simulations.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…However, influence of neoclassical transport has not been discussed so far. In our previous study, using a theoretical model, it is shown that the self-healing of islands is clearly reproduced, when the neoclassical transport-driven poloidal flows is taken into account [5]. In this paper, we report that such mechanism is actually observed in reduced fluid simulations.…”
Section: Introductionsupporting
confidence: 56%
“…In addition, the curvature driven current might be affected by non ideal effects. Based on the analytical theory [5], the shrink threshold of islands in the absence of the curvature effect is estimated as ν nc = 1.8 × 10 −4 , where the balance between the neoclassical force and the Lorentz force is essential in our parameters. This estimation is consistent with the simulations without the curvature effect.…”
Section: Nonlinear Simulationmentioning
confidence: 99%
“…[7][8][9] A different point is that the neoclassical viscosity due to the helical trapped particles is taken into account. [24][25][26][27][28] In tokamaks, the non-axisymmetric magnetic field perturbation by RMP drives the so-called neoclassical toroidal viscosity. 51 While, in stellarators, the ambient magnetic field has the considerable non-axisymmetric component (jB h j=B 0 $ 10 À1 ), which dominates the influence of RMP.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, by analogy with tokamaks, it has been attempted to explain the self-healing mechanism by the screening effect of helical trapped particle-induced neoclassical flows. [24][25][26][27][28][29] However, a problematic point is that, historically, the magnetic reconnection in stellarators (helical systems) has been investigated in the context of the curvature-driven tearing mode. The curvature-driven current perturbation, such as the resonant Pfirsch-Schl€ uter current, is excited by normal magnetic field line curvature, and magnetic islands are generated to sustain three-dimensional magnetohydrodynamics (MHD) equilibria.…”
Section: Introductionmentioning
confidence: 99%
“…While T V0 is used to denote the "viscous" torque, it should be noted that both cross-field viscosity and neoclassical damping physics are used to calculate this contribution to the steady-state torque balance relation. 42 In the limit z ¼ 0; k f ¼ 1. In this small island limit, the viscous torque can be interpreted as the being proportional to the jump in dX a =dq across the rational surface 13 as in the standard cylindrical case.…”
Section: Plasma Flows and Viscous Torquesmentioning
confidence: 99%